Evidence for children's error sensitivity during arithmetic word problem solving. (December 2015) - Lubin, Amélie; Houdé, Olivier; de Neys, Wim
Abstract: Solving simple arithmetic word problems is often challenging for children. Recent research suggests that children often fail to solve certain of these problems because they fail to inhibit erroneous heuristic intuitions that bias their judgment. However it is unclear whether these errors result from an error monitoring or inhibition failure. Our study focuses on this critical error detection. Eight to eleven year-old schoolchildren were given problems in which an intuitively cued heuristic answer conflicted with the correct answer and a control version in which this conflict was not present. After solving each version children were asked to indicate their response confidence. Results showed that children showed a sharp confidence decrease after having failed to solve the conflict problems. This indicates that erring children have some minimal awareness of the questionable nature of their answer and underscores that they have more arithmetic understanding than their errors might seem to suggest. Highlights: School-aged children often fail to solve arithmetic word problems. But do they err because of an error monitoring or inhibition failure? We study the nature of children's errors by measuring response confidence. Erring children have some minimal awareness of the debatable nature of their answers.